2010
DOI: 10.1016/j.epsl.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic lead in sediments of the Rotorua lakes, New Zealand

Abstract: Global atmospheric sources of lead have increased more than 100-fold over the past century as a result of deforestation, coal combustion, ore smelting and leaded petroleum. Lead compounds generally accumulate in depositional areas across the globe where, due to low solubility and relative freedom from microbial degradation, the history of their inputs is preserved. In lakes there is rapid deposition and often little bioturbation of lead, resulting in an excellent depositional history of changes in both natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The concentration of Si in lake bottom sediments was not determined in this study, but scanning electron microscopy (SEM) of Lake Rotorua sediments has shown that Aulacoseira granulata frustules comprise ~97% by volume of the sediment ( Fig. 2a; Pearson 2007, Pearson et al 2010. Rawlence and Reay (1976) also found the sediments of Lake Taupo were dominated by diatom frustules, predominantly Aulacoseira granulata and to a lesser extent Cyclotella stelliger, as were the sediments of Lake Okataina (Mauriohooho and Hendy, University of Waikato, unpubl.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of Si in lake bottom sediments was not determined in this study, but scanning electron microscopy (SEM) of Lake Rotorua sediments has shown that Aulacoseira granulata frustules comprise ~97% by volume of the sediment ( Fig. 2a; Pearson 2007, Pearson et al 2010. Rawlence and Reay (1976) also found the sediments of Lake Taupo were dominated by diatom frustules, predominantly Aulacoseira granulata and to a lesser extent Cyclotella stelliger, as were the sediments of Lake Okataina (Mauriohooho and Hendy, University of Waikato, unpubl.…”
Section: Study Sitementioning
confidence: 99%
“…Ejecta from recent eruptions form distinct tephra layers in the lake sediments and can be used to date the subsequent sediment deposition (Trolle et al 2008, Pearson et al 2010. These tephra also provide a source of Si to the lakes.…”
Section: Study Sitementioning
confidence: 99%
“…In Europe, anthropogenic atmospheric heavy metal source has dominated over the geogenic source since industrialization (Schotyk et al, 1998;De Vleeschouwer et al, 2007), but major issues remain about the sources of pollutant metals into aquatic environment. Moreover, some sediment deposits highly contaminated by past human activities (e.g., municipal and industrial waste sediment from wastewater treatment plants (WWTPs)) can present a potential health risk to a population through the possible remobilization of pathogens and inorganic pollutants at the sediment-water interface under the influence of chemical (e.g., changing redox conditions; Pearson et al, 2010) or physical (e.g., mass movement event or dam flushing; Girardclos et al, 2007;Wildi et al, 2004) processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Tarawera tephra has previously been described by Pullar and Kennedy [19] as a dark-coloured coarse material, which is very distinctive and can readily be distinguished visually within a sediment sample. Using tephras from volcanic eruptions has also been used by Trolle et al [11] and Pearson et al [20] to determine sedimentation rates following tephra deposition. Annual N load and 4-year average nitrogen load (t yr -1 ) to Lake Rotorua based on ROTAN R0 (present land use scenario) output.…”
Section: Sediment Parameterisationmentioning
confidence: 99%